The Impact of the COVID-19 Pandemic on the European Union Economy – Selected Issues - Iwona PAWLAS (Communications of International Proceedings, 2021)
The COVID-19 pandemic hit the world economy in 2020. The shock has been reflected in macroeconomic condition of national economies and in the intensity and structure of international relations. The main objective of the paper is to study and assess the impact of the COVID-19 pandemic on the European Union economy, and in particular to evaluate the economic situation in the European Union during the first year of the coronavirus pandemic. The parallel objective is to describe and assess the EU response to the pandemic. The research was conducted with the application of statistical data taken from EUROSTAT database and provided by Central Statistical Office. The following research methods were used: literature studies, critical thinking, documents examination, analysis and logical construction, comparative analysis of quantitative data. The conducted research and analysis made it possible to confirm hypothesis according to which the short-term economic consequences of the COVID-19 pandemic are visible both at the level of the European Union and in relation to its individual Member States, however, the scale of negative phenomena is very diversified. The negative economic consequences of the COVID-19 pandemic were reflected in the decline in GDP, reduction of industrial production and production in construction, decline in the value added in services, deterioration of the situation on the labor market, as well as the deterioration of public finance. The EU response to the pandemic evolved significantly over time.
Keywords: European Union; COVID-19 Pandemic; Economy; Policy Response.